PENDEKATAN ERGONOMI TOTAL DAN KEARIFAN LOKAL DALAM PERENCANAAN TEKNIS PENATAAN PURA DALEM BABADAN DESA ADAT TUMBAK BAYUH MENGWI-BADUNG - Sutarja, I.N.; Suditha, I.G.N.; Sudarsana, I.K.; Lanus, I.N.; Yana, A.A.G.A. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Sustainable development of Pura Dalem Babadan located in Desa Adat Tumbak Bayuh, Mengwi, Badung, requires technical planning arrangement of the temple compound in detail which include a clear layout, image detail and required budget plan. In the process of planning and designing the temple used two approaches: 1) total ergonomic approach (systemic approach, Holistic, Interdisciplinary and Participatory / SHIP assessed by appropriate technology) and 2) local wisdom approach. SHIP approach and the appropriate technology is applied in the selection of structural systems and materials, while the local wisdom approach applied in the selection of the layout and shape. This plan resulted in drawings neighborhood Dalem Babadan temple showing the overall layout of the building shrines along with other supporters, detail drawings of the building and the budget plan costs.